Pengaruh Intensitas Menonton Review Produk Scora dalam Live Streaming Tiktok @Scoraofficial dan Tingkat Kepercayaan Terhadap Keputusan Pembelian pada Mahasiswa di Kota Semarang - Mohamad Nor Fauzi; Kholifatun Rohmawati; Made Dwi Adnjani; Dian Marhaeni Kurdaningsih (INDO PUBLISHING, 2026)
The rapid development of TikTok's live streaming feature has opened new opportunities for brands to reach consumers directly. This study aims to analyze the influence of watching intensity and trust level on purchase decisions among university students in Semarang City. Using a quantitative method with 100 respondents and multiple linear regression analysis, the results show that watching intensity has a positive and significant effect on purchase decisions (t = 10.284 > t-table 1.984, sig. 0.000 < 0.05). Similarly, trust level also has a positive and significant effect (t = 11.531 > t-table 1.984, sig. 0.000 < 0.05). Simultaneously, both variables significantly influence purchase decisions (F = 125.747 > F-table 3.09, sig. 0.000 < 0.05), with a coefficient of determination (R²) of 0.722, indicating that 72.2% of purchase decisions are explained by both variables. This study concludes that higher watching intensity and trust level lead to greater likelihood of purchase decisions among students who watch SCORA product reviews on TikTok live streaming.